Model Strategi Fungsional dan Operasional dalam Penguatan Tata Kelola PTKIS - M. Hanif Satria Budi; Agus Zaenul Fitri; Sulistyorini (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
This study analyzes functional and operational strategy models in strengthening the governance of Private Islamic Religious Higher Education Institutions (Perguruan Tinggi Keagamaan Islam Swasta/ PTKIS), using a case study at the Faqih Asy’ari Islamic Institute (IAIFA) Kediri. In the context of the transformation of Islamic higher education, IAIFA serves as an example of the implementation of good university governance principles that integrate Islamic values with modern management practices. This research employs a descriptive qualitative approach with a case study method, utilizing interviews, observations, and institutional document analysis. The findings indicate that IAIFA’s functional strategies focus on three main aspects: transparent and efficient financial management, competency- and integrity-based human resource development, and the strengthening of public relations and marketing functions grounded in Aswaja values. Meanwhile, IAIFA’s operational strategies are implemented through the optimization of the performance of operational units, such as procurement, new student admissions, academic affairs, and student services. The implementation of these strategies reflects a synergy between strategic planning and technical execution in practice, which contributes to enhanced institutional effectiveness, efficiency, and accountability. Furthermore, the adoption of digital-based approaches in academic administration and student services demonstrates IAIFA’s responsiveness to the demands for innovation and governance modernization. This study confirms that the success of PTKIS governance is determined not only by managerial effectiveness but also by the integration of Islamic spiritual and ethical values across all dimensions of institutional management. The functional and operational strategy model of IAIFA Kediri may serve as a reference for other PTKIS in realizing professional, transparent, and sustainable Islamic higher education governance in the era of globalization.